Removal of cadmium by Lactobacillus kefir as a protective tool against toxicity - Gerbino, Oscar Esteban (2014)
The aim of this work was to evaluate the capacity of Lactobacillus. kefir strains to remove cadmium cations and protect eukaryotic cells from cadmium toxicity. Lb. kefir CIDCA 8348 and JCM5818 were grown in a 1/2 dilution of MRS broth supplemented with Cd(NO3)2 ranging 0 to 1 mM. Growth kinetics were followed during 76 hours at 30 °C by registering optical density at 600 nm every 4-10 hours. The accumulated concentration of cadmium was determined on cultures in the stationary phase by atomic absorption. The viability of a human hepatoma cell line (HepG2) upon exposure to a) free cadmium and b) cadmium previously incubated with Lb. kefir strains was evaluated by determining the mitochondrial dehydrogenase activity. Lb. kefir strains were able to grow and tolerate concentrations of cadmium cations up to 1 mM. The addition of cadmium to the culture medium increased the lag time in all the concentrations used. However, a decrease of the total biomass (maximum Absorbance) was observed only at concentrations above 0.0012 and 0.0011 mM for strains CIDCA 8348 and JCM 5818, respectively. Shorter and rounder lactobacilli were observed in both strains upon microscopic observations. Moreover, dark precipitates compatible with intracellular precipitation of cadmium were observed in the cytoplasm of both strains. The ability of Lb. kefir to protect eukaryotic cells cultures from cadmium toxicity was analysed using HepG2 cells lines. Concentrations of cadmium greater than 3x10-3 mM strongly decreased the viability of HepG2 cells. However, when the eukaryotic cells were exposed to cadmium pre-incubated 1 h with Lb. kefir the toxicity of cadmium was considerably lower, Lb. kefir JCM 5818 being more efficient. The high tolerance of Lb. kefir strains to cadmium concentrations largely exceeding the tolerated levels of cadmium for food (2.5 ug per kg of body weight) and water (3 ug/l) addressed to human consumption, is an important added value when thinking in health-related applications. Moreover, the protective effect on HepG2 cells supports the regular administration of Lb. kefir as an adequate and easy to implement strategy to prevent the harmful effects of cadmium in populations exposed to this toxic metal.